Eksekusi Putusan Pengadilan Dalam Perkara Perdata Di Pengadilan NegeriPurwokerto Kelas 1B - Aris Priyadi (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2023)
Court decisions must be enforceable or enforceable. Court decisions are meaningless if they cannot beimplemented. Therefore, the judge's decision has executorial power, namely the power to carry out what isstipulated in the decision, either voluntarily or under coercion by state instruments. Execution is theimplementation of a court decision that has obtained permanent legal force (in kracht van gewijsde) which iscarried out by force because the losing party in the case does not want to fulfill/obey the implementation of thecourt decision voluntarily. There are two forms of execution when viewed from the target to be achieved by thelegal relationship stated in the court decision, namely actual execution and execution of payment of a sum ofmoney. Purwokerto District Court Class 1 B, in the event that the execution has gone through an executionprocedure.